RELEVANSI HUKUM MENGHADIRI UNDANGAN WALI MATUL ‘URSY DI ERA MODERN: Perspektif Syekh Ibrahim Al-Bajuri - Ummu Sa’adah; Ilham Rosady , Muhammad (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2023)
This article will discuss a little about the implementation of the wali>matul 'ursy in the modern era, especially regarding the legal relevance of attending the wali>matul 'ursy invitation. In the current era, it is not uncommon for us to find cases that are actually prohibited by the shari'at but are generally accepted in modern society, these cases can actually become an obstacle to our obligation to attend the wali>matul 'ursy invitation, it could even be unlawful, in the sense that we can get sin for attending the event. This problem is rarely paid attention to by society in general, especially ordinary people who live far from the scientific world, especially in the field of shari'ah. Therefore the author will thoroughly examine this matter with a brief, concise and clear explanation. This type of research is library research using a descriptive qualitative approach. The data sources that the writer uses are turas books maz|hab Syafi'i, namely the Book of Hasyiyah al-Bajuri as the primary data source in this study. As a result of the research, the authors found the fact that the law of attending wali>matul 'ursy is conditionally obligatory. This means that if it does not meet the requirements then the obligatory law will move to permissible, makruh and even unlawful law.